Temporomandibular Joint Ankylosis in a Girl Child: Immunochemical Evaluation of Tissue Material Obtained from Repeated Arthroplasty Surgeries - Nityanand Jain; Mara Pilmane; Andrejs Skagers; Shivani Jain; Pavlo Fedirko (MDPI AG, 2023)
Temporomandibular joint ankylosis (TMJA) is a rare, but debilitating, condition that leads to TMJ joint hypomobility. Surgery is the mainstay for treatment, which is accompanied by rehabilitative and psychological support. Despite the advances in surgical techniques, the recurrence of TMJA post-surgery has been reported as a common complication. Therefore, it becomes essential to investigate and understand the histo-morpho-pathological processes governing these ankylotic changes. Given the lack of such studies in the literature, herein we present a case of a girl child who underwent primary surgery at the age of six years, followed by a second surgery at the age of twelve years. Ankylotic tissue samples collected during both surgeries were studied using various immunohistochemical markers for tissue remodeling, inflammation, antimicrobial activity, and transcriptional regulation. The expression of MMP-2 and -9 was downregulated in repeated surgery materials, whilst MMP-13 was rarely detected in both tissues. Strong MMP-8, TIMP-2, and TIMP-4 expressions were noted in both tissues, showing their anti-inflammatory and protective roles. Moderately strong expression of bFGF, FGFR-1, IL-1α, and TNF-α could indicate sustained tissue growth in the background of inflammation (wound healing). Interestingly, the expression of β-defensin-2 was found to be constant in both tissues, thereby indicating possible ECM remodeling and collagen breakdown. Finally, a moderate expression of RUNX-2, coupled with a low expression of WNT-1 and -3a, could indicate a slow and delayed bone regeneration process. Our results showcase the complex myriad of pathways that could be involved in the progression of TMJA and post-surgery healing processes. Immunopathological studies could aid in improving the diagnosis, treatment, and prognosis for patients affected with TMJA.